Quantity and Quality of Construction and Demolition Waste Materials in Kermanshah City, Iran - Jahangir Biglari; Shahin Kazemi; Rouhollah Shokri; Kamal Jalilian; Mitra Mohammadi (Shiraz University of Medical Sciences, 2023)
Background: The aim of this study was determination of the quantity and quality of construction and demolition waste materials in Kermanshah city, Iran.Methods: This descriptive cross-sectional research was carried out on eight urban areas in Kermanshah city from April to December in 2018. Due to the fact that in winter season, the C&D rate in Kermanshah is very low, data were not included in the study. Parameters of weight, volume, and density were calculated and presented in a seasonal average. The descriptive statistics were used to analyze the data in SPSS and Excel software.Results: More than 372.62 ton of waste materials were generated during the study, and the amount of concrete, bricks, soil, plaster, stone, ceramic, asphalt, and glass were approximately 31.49, 26.09, 23.45, 10.7, 3.37, 2.79, 2.07, and 0.0003%, respectively. According to the results, ferrous and non-ferrous metals, wood, plastic, paper, and cardboard have been recycled and sold due to their high economic value. Therefore, they were not in the C&D waste or were very little.Conclusion: With regards to the high volume of C&D waste generated, setting laws and regulations to reduce C&D waste should be considered to control optimally and efficiently the processes of production, collection, transportation, disposal, and recycling of waste.